ابن التركماني ومنهجه في كتاب التنبيه على أحاديث الهداية والخلاصة - Walid Mohd Said; Mohd. Fauzi Mohd. Amin; Syed Najihuddin Syed Hassan; Amran Abdul Halim; Abdulloh Salaeh; Nidzamuddin Zakaria; Mesbahul Hoque; Nor Saadah Musa (Fakulti Pengajian Quran dan Sunnah, 2024)
8TH International Prophetic Conference SWAN 2022 5th to 6th October 2022 (Hybrid Conference) Organized by: Faculty Of Quranic And Sunnah Studies